Fast Heavy‐Atom Tunneling in Trifluoroacetyl Nitrene. Issue 49 (8th November 2017) - Wu, Zhuang; Feng, Ruijuan; Li, Hongmin; Xu, Jian; Deng, Guohai; Abe, Manabu; Bégué, Didier; Liu, Kun; Zeng, Xiaoqing
Abstract: Chemical reactions involving quantum mechanical tunneling (QMT) increasingly attract the attention of scientists. In contrast to the hydrogen‐tunneling as frequently observed in chemistry and biology, tunneling solely by heavy atoms is rare. Herein, we report heavy‐atom tunneling in trifluoroacetyl nitrene, CF3 C(O)N. The carbonyl nitrene CF3 C(O)N in the triplet ground state was generated in cryogenic matrices by laser (193 or 266 nm) photolysis of CF3 C(O)N3 and characterized by IR and EPR spectroscopy. In contrast to the theoretically predicted activation barriers (>10 kcal mol −1 ), CF3 C(O)N undergoes rapid rearrangement into CF3 NCO with half‐life times of less than 10 min and unprecedentedly large 14 N/ 15 N kinetic isotope effects (1.18–1.33) in solid Ar, Ne, and N2 matrices even at 2.8 K. The tunneling disappearance of CF3 C(O)N becomes much slower in the chemically active toluene and in 2‐methyltetrahydrofuran at 5 K. Abstract : Tunnel vision : Trifluoroacetyl nitrene (CF3 C(O)N) in the triplet ground state was generated and characterized. In contrast to the theoretically predicted activation barrier of more than 10 kcal mol −1, the nitrene undergoes a fast [1, 2]‐CF3 shift into singlet trifluoromethyl isocyanate (CF3 NCO) through heavy‐atom tunneling in cryogenic matrices (2.8–23.0 K).